Reformed theology from Luther’s era engages digital-age challenges in twenty-first-century theological discourse within global contexts - Yanni Paembonan; Stevri P. N. Indra Lumintang (Institut Agama Kristen Negeri Toraja, 2025)
This research aims to build a dialogue between 16th-century Reformed theology and the challenges of 21st-century theology, especially in the context of the metaverse Church. The primary concern highlighted is the emergence of metaverse churches, which undermine the principle of physical communion within the Church. Consequently, how can principles of the Reformation, particularly the five Solas, offer a theological foundation for the Church to address digitalization in the context of metaverse churches, a significant theological challenge of the 21st century? Through historical-theological studies employing a qualitative approach and the serialization method. The concept of the metaverse Church presents opportunities to reach broader audiences, especially younger generations, yet it also risks diluting the sense of sacredness and physical community. The principle of sola Scriptura can serve as a basis for evaluating the use of technology in worship, while sola Fide and sola Gratia reaffirm the grace of salvation. Solus Christus emphasizes the centrality of Christ in the Christian faith, and soli Deo gloria directs faith life and counters moral relativism in the digital age. Thus, the spirit of the Reformation can provide a theological foundation for the Church to navigate modern challenges while preserving its faith identity.